Superposed Epoch Analysis of Nighttime Magnetic Perturbation Events Observed in Arctic Canada. Issue 9 (27th August 2021) - Engebretson, Mark J.; Ahmed, Lidiya Y.; Pilipenko, Viacheslav A.; Steinmetz, Erik S.; Moldwin, Mark B.; Connors, Martin G.; Boteler, David H.; Weygand, James M.; Coyle, Shane; Ohtani, Shin; Gjerloev, Jesper; Russell, Christopher T.
Abstract: Rapid changes of magnetic fields associated with nighttime magnetic perturbation events (MPEs) with amplitudes |ΔB| of hundreds of nT and 5–10 min duration can induce geomagnetically induced currents (GICs) that can harm technological systems. Here we present superposed epoch analyses of large nighttime MPEs (|dB/dt| ≥ 6 nT/s) observed during 2015 and 2017 at five stations in Arctic Canada ranging from 64.7° to 75.2° in corrected geomagnetic latitude (MLAT) as functions of the interplanetary magnetic field (IMF), solar wind dynamic pressure, density, and velocity, and the SML, SMU, and SYM/H geomagnetic activity indices. Analyses were produced for premidnight and postmidnight events and for three ranges of time after the most recent substorm onset: (a) 0–30 min, (b) 30–60 min, and (c) >60 min. Of the solar wind and IMF parameters studied, only the IMF Bz component showed any consistent temporal variations prior to MPEs: a 1–2 h wide 1–3 nT negative minimum at all stations beginning ∼30–80 min before premidnight MPEs, and minima that were less consistent but often deeper before postmidnight MPEs. Median, 25th, and 75th percentile SuperMAG auroral indices SML (SMU) showed drops (rises) before pre‐ and post‐midnight type A MPEs, but most of the MPEs in categories B and C did not coincide with large‐scale peaks in ionospheric electrojets. Median SYM/H indices were flat near −30 nT for premidnight events and showed no consistent temporal association with any MPE events. More disturbed values of IMF Bz, Psw, Nsw, SML, SMU, and SYM/H appeared postmidnight than premidnight. Key Points: Superposed epoch analyses of 2 years of >6 nT/s magnetic perturbation events (MPEs) from 5 high latitude Arctic stations are presented Of the solar wind and interplanetary magnetic field (IMF) parameters studied, only IMF Bz showed any consistent pattern: a drop and rise prior to MPE occurrence Most of the MPEs that occurred more than 30 min after a substorm onset did not coincide with peaks in the westward electrojet